2008
DOI: 10.1590/s0100-67622008000600001
|View full text |Cite
|
Sign up to set email alerts
|

RAPD analysis of genetic variability in a multiprovenance base population of Eucalyptus grandis hill ex maiden

Abstract: -This study aimed to evaluate the genetic variability among individuals of a base population of Eucalyptus grandis and to build a molecular marker database for the analyzed populations. The Eucalyptus grandis base population comprised 327 individuals from Coff's Harbour, Atherton and Rio Claro. A few plants came from other sites (Belthorpe MT. Pandanus, Kenilworth, Yabbra, etc.). Since this base population had a heterogeneous composition, the groups were divided according to geographic localization (latitude a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…SPAs and native seedlots evaluated in this study had relatively higher number of alleles and PIC compared to CSOs, indicating the genetic quality of seed from different sources. Leite et al (2008) reported higher diversity in SPA progenies than wild E. grandis populations and 11 % lower diversity in CSO progeny compared to SPA. Offspring from clones harbor more diversity than the parent clones especially with regard to number of alleles in deployed crop (Ingvarsson and Dahlberg, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…SPAs and native seedlots evaluated in this study had relatively higher number of alleles and PIC compared to CSOs, indicating the genetic quality of seed from different sources. Leite et al (2008) reported higher diversity in SPA progenies than wild E. grandis populations and 11 % lower diversity in CSO progeny compared to SPA. Offspring from clones harbor more diversity than the parent clones especially with regard to number of alleles in deployed crop (Ingvarsson and Dahlberg, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…observed 0.40 for E. urophylla;Leite et al (1997) 0.67 for E. grandis; Pigato and Lopes (2001) 0.36 for E. urophylla; and Leite et al (2002) observed a mean distance of 0.68 for E. urophylla as well.…”
mentioning
confidence: 94%